Assessing the contribution of livestock systems to development in drylands: indicators for appropriate public policies - Alary, Véronique; Gautier, Denis (Perspective, 2023)
Version française de l'article In drylands, scientific research shows that mobile livestock systems derive the maximum social, environmental and economic benefits from these areas. These systems ensure both short-term security in case of shocks and, in the right conditions, investment capacity. However, it is difficult to develop indicators to understand and assess their contribution to territorial development, as they sit at the intersection between several scales of space and time, as well as of social and institutional organisation. The operational framework proposed here is aimed at rethinking the role of livestock systems in the sustainability of resources and societies in drylands. Six types of development indicators compare these three dimensions: characteristics of herds and of goods and services provided by the species bred, herd size, herd management system, management of land and resources use, access to state support, and dependence on markets. This framework invites policymakers to integrate these different scales in order to understand the adaption mechanisms and the risks associated with intervention.